First Record of the Ricefish, Oryzias haugiangensis (Adrianichthyidae: Oryziinae), from Southeastern Thailand - MAGTOON, WICHIAN (Tropical Natural History, 2011)
Specimens of the ricefish, Oryzias haugiangensis, reported here for the first time from the brackish waters in the southeastern Thailand, were caught in a mangrove forest habitat. This study compares the morphometric and meristic characters and the karyotype of O. haugiangensis with those of the Andaman sea specimens of O. javanicus which are clearly distinguishable by the length of the snout, head, preanal, preanal fin, prepelvic fin and anal fin base, plus the body depth at the anterior of the anal fin origin. Oryzias haugiangensis is similar to O. javanicus in the number of pelvic fin and branchiostegal rays present, and in the diploid chromosome number (2n = 48), but differs from the latter in that it has a lower number of anal fin and pectoral fin rays and has a different karyotype, with 2n = 48 (2 SM + 23 A; NF = 54). Oryzias haugiangensis belongs to monoarmed chromosome group within the genus Oryzias.